(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
The CAT 3512 engine block cylinder is one of the main components in a Perkins engine structure, often damage to the cylinder block surface even reaches the limit on the cylinder block surface, then metal spray and grinding processes are carried out to restore the surface size to like new and can be used immediately. The purpose of this study was to determine the roughness value with the metal spray method on the surface of the cylinder block using the Proth PSGO engine. This research uses quantitative methods with stages of literacy, observation, and field documentation. Located at PT Bumi Intan Gemilang with the research sample being the CAT 3512 engine block. The independent variables in this study were the 3 point RH test and the 3 point LH test on the cylinder block surface using an aluminum oxide grinding stone. The dependent variable in this study is the surface roughness of the cylinder block by testing the roughness Ra (roughness average). And the control variable in this research is the milling speed of 1.000 rpm. The results of this study based on measurements yielded an average roughness value of 0,7215 µm, the average roughness value at 0,6 mm infeed was 5,4205 µm. At 0,2 mm finishing feeding, the value is 0,7215 µm, this value includes the specified value so that the machine can operate and is suitable for reuse.